2014
DOI: 10.17221/518/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the contents of vitamins A and E during the ripening of cheeses with different compositions

Abstract: Revilla I., Lobos-Ortega I., Vivar-Quintana A., González-Martín M.I., Hernández-Hierro J.M., González-Pérez C. (2014): Variations in the contents of vitamins A and E during the ripening of cheeses with different compositions. Czech J. Food Sci., 32: 342-347.We investigated the composition in vitamins A and E of cheeses made from the milks of ewes, goats and cows. A total of 84 cheeses of known composition were prepared and controlled to determine the influence of different factors, e.g. the variable proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
(32 reference statements)
3
12
1
1
Order By: Relevance
“…However, in ewe milk, β-carotene is fully converted into retinol, as mentioned previously. Finally, unlike previous reports (Lucas et al, 2006b(Lucas et al, , 2008a, no significant correlation was found between TEAC and α-tocopherol; the cheeses analyzed in the current trial did not show differences in α-tocopherol due to animal species, season, or ripening stage (Revilla et al, 2014).…”
Section: Correlation Studiescontrasting
confidence: 93%
See 3 more Smart Citations
“…However, in ewe milk, β-carotene is fully converted into retinol, as mentioned previously. Finally, unlike previous reports (Lucas et al, 2006b(Lucas et al, , 2008a, no significant correlation was found between TEAC and α-tocopherol; the cheeses analyzed in the current trial did not show differences in α-tocopherol due to animal species, season, or ripening stage (Revilla et al, 2014).…”
Section: Correlation Studiescontrasting
confidence: 93%
“…In some cheeses, antioxidant activity has been correlated with contents of vitamin E and β-carotene (Lucas et al, 2006 a,b). In agreement with this, the summer cheeses in our trials were characterized by a higher content of vitamin A (Revilla et al, 2014). Moreover, previous works in similarly manufactured cheeses reported that summer cheeses had higher total contents of watersoluble peptides (Vivar-Quintana et al, 2009) and a lower fat content (González-Martín et al, 2011b).…”
Section: Effects Of Animal Species Season and Ripeningsupporting
confidence: 90%
See 2 more Smart Citations
“…Research [ 5 , 16 , 17 , 18 ] indicates that the quality of raw milk is one of the main determinants of the value of dairy products, including curd cheese. Only high-quality raw milk with an appropriate chemical composition will result in a product with optimal nutritional value and health-promoting properties that fully meets consumer expectations [ 19 ].…”
Section: Introductionmentioning
confidence: 99%